2006
DOI: 10.1021/bi060722o
|View full text |Cite
|
Sign up to set email alerts
|

Differential Membrane Packing of Stereoisomers of Bis(monoacylglycero)phosphate

Abstract: Bis(monoacylglycero)phosphate (BMP) reveals an unusual sn-1,sn-1′ stereoconfiguration of glycerophosphate. We synthesized sn- (3-myristoyl-2-hydroxy)glycerol-1-phospho-sn-1′-(3′-myristoyl-2′-hydroxy)glycerol (1,1′-DMBMP) and characterized the thermotropic phase behavior and membrane structure, in comparison with those of the corresponding sn-3:sn-1′ stereoisomer (3,1′-DMBMP), by means of differential scanning calorimetry (DSC), small-and wide-angle X-ray scattering (SAXS and WAXS, respectively), pressure-area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 74 publications
3
32
0
Order By: Relevance
“…As observed in Fig. 4F, 14BMP displays two endothermic peaks on heating, a small transition at about 19°C from a quasicrystalline phase L c1 to a quasi-crystalline phase with different tilt angle L c2 and a main transition at about 41°C from a quasi-crystalline phase L c2 to the liquid phase L α [53]. The incorporation of NS4B AH2 into 14BMP membranes at a lipid/peptide ratio of 15:1 did not alter the thermotropic behavior of the phospholipid, since no significant effect was observed on the two transitions of 14BMP (Fig.…”
Section: Resultsmentioning
confidence: 58%
“…As observed in Fig. 4F, 14BMP displays two endothermic peaks on heating, a small transition at about 19°C from a quasicrystalline phase L c1 to a quasi-crystalline phase with different tilt angle L c2 and a main transition at about 41°C from a quasi-crystalline phase L c2 to the liquid phase L α [53]. The incorporation of NS4B AH2 into 14BMP membranes at a lipid/peptide ratio of 15:1 did not alter the thermotropic behavior of the phospholipid, since no significant effect was observed on the two transitions of 14BMP (Fig.…”
Section: Resultsmentioning
confidence: 58%
“…1,2,3-Tridocosahexaenoyl-sn-glycerol (tri22:6-TG) was from Polariz (Pleuven, France). sn-(3-Pentadecanoyl-2-hydroxy)-glycerol-1-phospho-sn-1′-(3′-pentadecanoyl-2′-hydroxy)-glycerol (15:0/15:0-BMP) and sn-(3-docosahexaenoyl-2-hydroxy)-glycerol-1-phosphosn-1′-(3′-docosahexaenoyl-2′-hydroxy)-glycerol (22:6/22:6-BMP) were chemically synthesized by our chemist colleagues according to the method previously described (30). [1a,2a(n)- …”
Section: Methodsmentioning
confidence: 99%
“…Kobayashi and colleagues showed that BMP plays a role in the formation, structure, and traffi cking of endosomal/lysosomal compartments in cells under normal conditions ( 3,57,59 ). Late endosomes/lysosomes form multivesicular bodies under normal conditions, but form multilamellar vesicles in pathological cases such as the gangliosidoses ( 60,61 ). Both gangliosides and BMP are thought necessary for the formation of these aberrant lamellar bodies.…”
Section: Bmp Separates From Its Structural Isomer Pg By Hptlc and Masmentioning
confidence: 99%